Die betekenis van die kerklike dogma - Koekemoer, J. H. (Hervormde teologiese studies, 1991)
The meaning of the dogma Because dogmatic decisions of the past are not guaranteed to remain relevant for contemporary temptations and attacks, and because the dogma is by intrinsically relative to the Word of God, this article argues that a critical interpre tation of the dogma is essential. The purpose of such a critical interpretation must be to keep dogma relevant and alive. Therefore questions like the origin of the dogma, the essence of the dogma, the hermeneutics of the dogma and the task of dogmatics, should be answered.